Minat Kunjungan Wisatawan Pada Aktivitas Wisata di Taman Nasional Way Kambas Kabupaten Lampung Timur Provinsi Lampung - Kasmin Kasmin; Lymbarski Caesariano (Universitas Negeri Padang, 2022)
Way Kambas National Park is an elephant protection national park located in Lampung, Indonesia. Interest in visiting tourists is an important thing that needs to be considered, Way Kambas national park is a tourist attraction that has potential. Several kinds of tourist activities can be found at the Way Kambas tourist attraction. Among these activities, it is known that Walking in The Rice Field received the highest appreciation, namely as many as 32 respondents (64%) of the 50 respondents from foreign tourists who were taken as samples, followed by the Attending Culture Events activity as many as 29 respondents (58%), followed by the respective activities. each Sightseeing 26 respondents (52%), Spa/Relaxation 24 (48%), Shopping 23 respondents (46%), Cycling 14 (28%), Tracking 11(22%), Cooking Class 10 (20%), Jogging 9 (18%), Dancing Class 5 (10%), others (eating at local restaurants and stalls) 2 respondents (4%), and finally 2 respondents (4%) namely Painting Class activities. The research location was conducted in Way Kambas National Park (TNWK). This research is qualitative research with an interview, observation, and documentation data collection techniques. The sample of this study is data on tourist visits sourced from the Way Kambas National Park Hall. The results of the study found that tourism activities in Way Kambas National Park influenced the interest of visiting local and foreign tourists.